Korelasi resipokral ekologi dengan manusia pada novel Aroma Karsa karya Dee Lestari - Ichda Nabilatin Nisa; Eggy Fajar Andalas (Universitas Ahmad Dahlan, 2020)
Human relationships will not be able to escape with the natural ecosystem. Humans and natural ecosystems coexist in a balanced portion so that no gaps occur. A reciprocal relationship between human life and the natural ecosystem occurs. However, the relationship between humans and the natural ecosystem becomes unhealthy because the human being can not keep the natural well. The research aims to find a reciprocal relationship between humans and the natural ecosystem and discover the human role of the natural ecosystem that has helped human life. To solve the problem, this study uses the human ecological approach and uses environmental posityism theory (Vidal de la Blache). The source of this research data is the novel Aroma Karsa by Dee Lestari published in 2018 and uses the novel behind the Curtain Aroma Karsa by Dee Lestari published in 2019 as an additional interpretation of research. Both novels are published by PT Landforms Pustaka. The data collection techniques used are the records. The research data analysis technique uses data presentation, data reduction and withdrawal of conclusions. The results of this research are first, the reciprocal relationship found is that human party can take advantage of nature which is used for livelihood, beauty products, product of scholarship, treatment material, and become the source of life. Secondly, the human role of the ecosystem is to safeguard, nurture, and preserve the natural ecosystem from being extinct and to fulfill human life in the future.